Pemasaran Online melalui Media TikTok Usaha Kebab Arab Obama di Kelurahan Pagar Dewa - Susanti, Neri; Fitriano, Yun; Herlina, Yeni; Lesmana, Rendy (Jurnal Gotong Royong, 2025)
iThis research discusses the use of TikTok as an online marketing platform for the culinary business Kebab Arab Obama in Pagar Dewa. The study aims to explore how digital marketing through TikTok can support micro-businesses by leveraging existing community assets. Employing the AssetiBasediCommunity Development (ABCD) method, this study focuses on identifying community strengths and digital trends that can enhance the business's outreach. Data were collected through interviews, observation, and digital content analysis. The findings show that TikTok effectively increases brand visibility and sales when content is tailored to local culture and consumer behavior. The ABCD approach proves effective in mobilizing community involvement to support local entrepreneurship through digital means.